Avaliação do emprego de agregados alternativos em microrrevestimento asfáltico - Castro, Pedro Bastos de (2014)
Microsurfacing is a type of bituminous wearing course applied in pavement preventive maintenance that has been used successfully in states of Brazil and the world, but cannot be applied in structurally deficient pavements. For microsurfacing composition it is used local aggregates that in some cases become scarce and expensive. This situation has motivated researchers to study new materials to be used this bituminous wearing course. Therefore, the main objective of the present research is to verify the technical, economic and environmental viability of using steel slag and recycled asphalt aggregates in microsurfacing applications. To reach the main objective, a laboratory procedure was developed in four steps. In the first step, the collection and characterization of conventional and alternative aggregates (steel slag and recycled asphalt aggregates) and polymer-modified emulsified asphalt were made. In the second step, mix desing, surface abrasion resistance and set time tests were performed. In the third step, the microsurfacing performance was analyzed by a laboratory traffic simulator when it is applied over a base material with a known mechanical behavior. In the fourth step, a comparative cost study of microsurfacing application using conventional and alternative aggregates was performed. The laboratory procedure results indicated that the alternative aggregates studied have the potential to be used in microsurfacing aplications without service life decreasing, providing a reduction in implementation costs.